ALA6, a P4-type ATPase, Is Involved in Heat Stress Responses in Arabidopsis thaliana - Niu, Yue; Qian, Dong; Liu, Baiyun; Ma, Jianchao; Wan, Dongshi; Wang, Xinyu; He, Wenliang; Xiang, Yun (Frontiers in Plant Science, 2017)
Maintaining lipid membrane integrity is an essential aspect of plant tolerance to high temperature. P4-type ATPases are responsible for flipping and stabilizing asymmetric phospholipids in membrane systems, though their functions in stress tolerance are not entirely clear. Aminophospholipid ATPase6 (ALA6) is a member of the P4-type ATPase family, which has 12 members in Arabidopsis thaliana. Here, we show that a loss-of-function mutant of ALA6 (ala6) exhibits clear sensitivity to heat stress, including both basal and acquired thermotolerance treatments. Overexpression of ALA6 improves seedling resistance to heat stress, while mutated ALA6 transgenic plants, in which the conserved functional site of the ALA family has a point mutation, are still susceptible to heat stress like ala6 loss-of-function mutant. In addition, ala6 displays higher ion-leakage during heat treatment, suggesting that the lipid flippase activity of ALA6 plays a vital role in heat stress responses. Transcriptome analysis reveals differences in gene expression between ala6 and wild-type plants with or without heat stress. The differentially expressed genes are involved primarily in the physiological processes of stress response, cellular compartment maintenance, macromolecule stability and energy production. Our results suggest that ALA6 is crucial for the stability of membrane when plants suffer from high temperature stress.